The Analysis of the Effect of Financial Deepening on Indonesia’s Economic Growth: A Longitudinal Analysis - Muhammad Afan Subkhan; Dinar Melani Hutajulu (LifeSciFi, 2023)
Economic development cannot be separated from the financial sector. Financial deepening has been identified as a way to accelerate economic growth. The purpose of this study was to analyze the effect of financial deepening, the rupiah exchange rate and interest rates on economic growth in Indonesia in 1995-2018. This study uses secondary time series data from the World Bank. This study uses Error Correction Model (ECM) analysis through the EViews 10 program. The results of this study indicate that the performance of the financial sector in Indonesia is still shallow. In the long and short term, financial deepening and exchange rates have a negative and significant effect. Meanwhile, interest rates have a positive and significant effect on economic growth both in the long term and in the short term.